Cerebrovascular effects of endothelin-1 investigated using high-resolution magnetic resonance imaging in healthy volunteers. Issue 8 (August 2020) - Hougaard, Anders; Younis, Samaira; Iljazi, Afrim; Haanes, Kristian A; Lindberg, Ulrich; Vestergaard, Mark B; Amin, Faisal M; Sugimoto, Kazutaka; Kruse, Lars S; Ayata, Cenk; Ashina, Messoud
Endothelin-1 (ET-1) is a highly potent vasoconstrictor peptide released from vascular endothelium. ET-1 plays a major role in cerebrovascular disorders and likely worsens the outcome of acute ischaemic stroke and aneurismal subarachnoid haemorrhage through vasoconstriction and cerebral blood flow (CBF) reduction. Disorders that increase the risk of stroke, including hypertension, diabetes mellitus, and acute myocardial infarction, are associated with increased plasma levels of ET-1. The in vivo human cerebrovascular effects of systemic ET-1 infusion have not previously been investigated. In a two-way crossover, randomized, double-blind design, we used advanced 3 tesla MRI methods to investigate the effects of high-dose intravenous ET-1 on intra- and extracranial artery circumferences, global and regional CBF, and cerebral metabolic rate of oxygen (CMRO2 ) in 14 healthy volunteers. Following ET-1 infusion, we observed a 14% increase of mean arterial blood pressure, a 5% decrease of middle cerebral artery (MCA) circumference, but no effects on extracerebral arteries and no effects on CBF or CMRO2 . Collectively, the findings indicate MCA constriction secondarily to blood pressure increase and not due to a direct vasoconstrictor effect of ET-1. We suggest that, as opposed to ET-1 in the subarachnoid space, intravascular ET-1 does not exert direct cerebrovascular effects in humans.